Smart moves : why learning is not all in your head - Hannaford, Carla, 1944- (Great River Books, 2005)
"Smart Moves. The body's role in thinking and learning is presented for the first time in a popular readable format, thoroughly supported by scientific research. Neurophysiologist and educator Carla Hannaford tells us why we must move -- and shows us how to move to fully activate our learning potential. Her remarkable insights will be of great and immediate value to learners of all ages, from the gifted to the so-called learning-disabled. Book jacket."--Jacket.